Maize Breeding: From Domestication to Genomic Tools - Leon Muntean; Andreea Ona; Ioana Berindean; Ionuț Racz; Sorin Muntean (Agronomy, 2022)
Maize will continue to expand and diversify as an industrial resource and a feed and fuel crop in the near future. The United Nations estimate that in 2050 the global population will reach 9.7 billion people. In this context, food security is increasingly being discussed. Additionally, another threat to food security is global warming. It is predicted that both the quantity and the quality of crops will be seriously affected by climate change in the near future. Scientists and breeders need to speed up the process of creating new maize cultivars that are resistant to climate stress without diminishing yield or quality. The present paper provides a brief overview of some of the most important genomics tools that can be used to develop high-performance and well-adapted hybrids of maize and also emphasizes the contribution of bioinformatics to an advanced maize breeding. Genomics tools are essential for a precise, fast, and efficient breeding of crops especially in the context of climate challenges. Maize breeders are able now to develop new cultivars with better traits more easily as a result of the new genomic approaches, either by aiding the selection process or by increasing the available diversity through precision breeding procedures. Furthermore, the use of genomic tools may in the future represent a way to accelerate the processes of de novo domestication of the species.